The Cost of Technology Transfer in Construction Companies (In Iraq) (Journal of Engineering, 2023)
The construction sector is considered an important and influential pivot in the national economy of any country.  Nations are working to develop this sector, receiving modern and developed techniques. So, this sector can be a carrier or a receiver of modern technologies. The cost of technology transfer between the international companies that sponsor this sector is a matter of great importance, especially since different factors affect the need for this advanced technology. The cost of technology transfer in construction is related to multiple factors presented by Knowledge, equipment, plant, hardware and software. The lack of distinguishing and evaluating the direct and indirect costs in the construction sector during technology transfer may lead to infractions in the company's budget. This manuscript aims to investigate the direct and indirect costs of transferring technology and the major factors constrained by this process. This work adopted a theoretical study and investigated the opinions of experts and engineers (by questionnaire) working in different construction sites. This Manuscript showed that the largest weight of the cost for both modern equipment and counsulant/designers is a direct cost and indirect cost, respectively, for transferring technology in the construction sector.